THE IMPORTANCE OF TAXES IN REGULATING THE ECONOMY (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article talks about how taxes can make the economy go bad. First of all, I will give information about how taxes appeared and in which period, in which region, what types of taxes were there, and in what order the state collected them from the population. Then, I will give information about the importance of taxes today, and what tasks they perform, as well as their different types.